New long-stemmed eocrinoid from the Furongian Point Peak Shale Member of the Wilberns Formation, central Texas. (9th March 2015) - Zamora, Samuel; Sumrall, Colin D.; Sprinkle, James
Abstract: Llanocystis wilbernsensis n. gen. n. sp. (Eocrinoidea, Echinodermata) is described based on three specimens from the Furongian Point Peak Shale Member of the Wilberns Formation in central Texas. It displays a unique morphology including a very long stem constructed with holomeric columnals, few feeding appendages, and a polyplated theca. The specimens occur in an intraformational conglomerate deposited in a proximal carbonate platform environment and represent an example of the poorly documented "pelmatozoan" radiation that occurred in proximal facies by the end of the Cambrian.